(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The COVID-19 pandemic indicated the strengths and weaknesses of the organization of health systems in various countries, identified the problems of ensuring the safety of the population with the spread of infectious diseases, provided lessons and conclusions, and indicated the most effective measures to combat the infection. The main lesson and an effective way to combat a pandemic is the principle of the maximum possible quarantine measures at the state level, the mobilization of medical personnel, the provision of sufficient space, medicines, reagents, apparatus and devices, personal protective equipment, the achievement of population immunity, and vaccination.